2015
DOI: 10.1016/j.meatsci.2015.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neck cut position on time to collapse in halal slaughtered cattle without stunning

Abstract: This study examined the effect of neck cut position on the time to physical collapse in upright restrained halal slaughtered cattle (n = 644). Time to collapse was used as an indirect indicator of the early stages of onset of unconsciousness. Cattle were slaughtered with either a conventional low (LNC) (n=561) or a high neck cut (HNC) (n = 83). Mean time to final collapse was higher in the LNC compared to HNC group (18.9 ± 1.1s and 13.5 ± 1.3s respectively (P < 0.01)). The mean false aneurysm scores were highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 23 publications
1
39
0
1
Order By: Relevance
“…penetrative captive bolt stunning, gas stunning and electric head-to-body stunning where the voltage spans the heart). The use of reversible stunning for Halal production is widely accepted by the Muslim community in New Zealand (Gilbert et al 1986), within the European Union (Dialrel 2010;Food Standard Agency 2012, 2015 and in some Muslim majority countries (MS1500 2009MUI HAS 23103, 2012). The main reason for the approval of reversible stunning is that it ensures that a live and unconscious but otherwise essentially undamaged animal is presented at the final slaughter operation where it is exsanguinated.…”
Section: Pre-slaughter Stunningmentioning
confidence: 99%
See 1 more Smart Citation
“…penetrative captive bolt stunning, gas stunning and electric head-to-body stunning where the voltage spans the heart). The use of reversible stunning for Halal production is widely accepted by the Muslim community in New Zealand (Gilbert et al 1986), within the European Union (Dialrel 2010;Food Standard Agency 2012, 2015 and in some Muslim majority countries (MS1500 2009MUI HAS 23103, 2012). The main reason for the approval of reversible stunning is that it ensures that a live and unconscious but otherwise essentially undamaged animal is presented at the final slaughter operation where it is exsanguinated.…”
Section: Pre-slaughter Stunningmentioning
confidence: 99%
“…In some cases, after the Shechita cut, some cattle have attempted to escape after initially collapsing (Levinger, 1976). It has been suggested that a higher neck cut position (above the conventional neck cut position) can reduce the incidence of false aneurysms (Gregory et al, 2012, Gibson et al, 2015 particularly during Halal slaughter without the use of thoracic sticking. In fact Gibson et al (2015) showed that performing a high neck cut during Halal slaughter without stunning significantly reduced the time to final collapse of cattle.…”
Section: Thoracic Stickingmentioning
confidence: 99%
“…Ainsi, la durée de ces procédures, la densité dans le camion, le type de conduite et de routes empruntées, les températures et les courants d'air sont autant de paramètres connus pour influencer l'état de stress des bovins. L'efficacité des techniques d'étourdissement et de saignée, notamment en termes de rapidité d'induction de l'inconscience, ont également fait et font encore l'objet de nombreuses études (European Food Safety Authority [EFSA], 2004;Gregory et al 2007;Gibson et al 2015;Terlouw et al 2015 a et b). Ces travaux concernent essentiellement l'évaluation de l'inconscience et l'efficacité du geste lors de la saignée afin de réduire au maximum le stress et les douleurs.…”
Section: Contexte Scientifiqueunclassified
“…Sheep that are slaughtered without stunning lose consciousness 2-24 seconds after the neck cut (Gregory and Wotton, 1984;Devine et al, 1986;. Consciousness in cattle is generally lost later than in sheep and ranges from 2 s up to over 5 minutes after the neck cut (Nangeroni and Kennett, 1963;Newhook and Blackmore, 1982;Daly et al, 1988;Gibson et al, 2015;Verhoeven et al, 2016a). There is debate about the extent to which slaughter of conscious, i.e.…”
Section: Scientific Contributions To Ethical Concerns With Regards Tomentioning
confidence: 99%
“…In total 15 of 82 (18%) calves in that study were cut a second time and one of those 15 calves was cut a third time. Recent studies in cattle suggest that bleed out is improved when the carotid arteries in the neck are severed at the position of the first cervical vertebrae (C1) instead of C2 to C4 (Gregory et al, 2012a, Gibson et al, 2015. Multiple reasons have been proposed to why bleeding out may be improved when the neck is cut at the C1 position.…”
Section: Non-stunned Slaughtermentioning
confidence: 99%